Evaluate Short-Term Outcomes of abciximab in ST-Segment Elevation Myocardial Infarction Patients Undergoing Percutaneous Coronary Intervention: A Meta-Analysis of Randomized Clinical Trials - Nan Bai; Ying Niu; Ying Ma; Yao-Sheng Shang; Peng-Yu Zhong; Zhi-Lu Wang (Journal of Interventional Cardiology)
Objectives. This meta-analysis was to verify the short-time efficacy and safety of abciximab in patients with ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI). Background. Abciximab has long-term efficacy in patients with STEMI undergoing PCI, but the short-term efficacy is still controversial. Methods. We conducted a systematic review and meta-analysis compared with or without abciximab in patients with STEMI undergoing PCI. The relevant randomized controlled trials were included by searching PubMed, EMBASE, Cochrane Library, and Web of Science databases and other sources. The relative risk (RR) and 95% confidence intervals (CI) of outcomes were calculated by the fixed-effects model. Results. Ten randomized controlled trials with 5008 patients met inclusion criteria. There were no significant differences in risk of all-cause death at 30-day (RR 0.79, CI 0.55–1.12, P=0.18), major bleeding (1.37, 0.93–2.03, P=0.11), and transfusion (1.23, 0.94–1.61, P=0.13) between the two groups. However, there were significant differences in risk of all-cause death at 6 months (0.57, 0.36–0.90, P=0.02), recurrent myocardial infarction (0.55, 0.33–0.92, P=0.02), repeat revascularization (0.58, 0.43–0.78, P=0.0004), final TIMI flow <3 (0.77, 0.62–0.96, P=0.02), minor bleeding (1.29, 1.02–1.63, P=0.04), and thrombocytopenia (2.04, 1.40–2.97, P=0.0002). Conclusions. The application of abciximab can lead to a lower risk of reinfarction, revascularization, and all-cause death at 6 months, but a higher risk of minor bleeding, and thrombocytopenia.